Mittelstädte als Stabilisatoren ländlich-peripherer Räume. - Ries, Elke Jana (My University, 2019)
Die Arbeit widmet sich einer Untersuchung der regionalen Stabilisierungsfunktion von Mittelstädten für ländlich-periphere Räume einschließlich einer Analyse der Möglichkeiten und Grenzen deren Aufrechterhaltung unter den Einflüssen sozioökonomischer Transformationsprozesse und den damit verbundenen Anpassungsbedarfen. Darauf aufbauend umfasst sie eine Analyse zur Identifikation von Erfolgsfaktoren, die mittelstädtische Stabilisierungsfunktionen in ländlich-peripheren Räumen zukünftig sicherstellen. Hierzu widmet sich die Arbeit zunächst einer definitorischen Einordnung des Stabilisierungsbegriffs in den Regionalwissenschaften. Eng verknüpft ist damit einhergehend die Analyse landes- und regionalplanerischer sowie regionalökonomischer Ansätze unter dem Blickwinkel ihres Stabilisierungsgedankens sowie die Untersuchung von bestehenden Strategien zum Umgang mit regionalen Strukturwandelprozessen. Daran anknüpfend erfolgt eine indikatorenbasierte beziehungsweise funktionale Typisierung des Stadttypus Mittelstadt im Kontext des ländlich-peripheren Raumtypus. Damit einhergehend wird fünf ausgewählten Fallstudien eine vertiefende Evaluation zugeführt. Hierdurch ergeben sich ergänzende Erkenntnisse insbesondere im Hinblick auf Verflechtungen zwischen Kreisregion und Mittelstadt, auf den Bedeutungsgrad der Mittelstadt bezüglich ihrer Wohn-, Arbeitsplatz- und Versorgungszentralität sowie insbesondere im Hinblick auf bestehende Handlungserfordernisse sowie Entwicklungsstrategien und Handlungsansätze zur Stärkung der Funktion und Rolle der Mittelstadt in und für ihr ländlich-peripheres Umfeld.

Socio-economic trends that are highly relevant for spatial planning are the basis for future issues affecting regions and municipalities. At the same time, an ongoing process of urbanisation and increasingly differentiated and sometimes highly divergent development dynamics are leading to an increase in regional imbalances. This development raises questions about how the guiding principle of equality in living conditions can be safeguarded. In this context, medium-sized cities in particular are seen as regional anchors, especially for structurally weak and peripheral regions. At the same time, medium-sized towns in peripheral rural regions are experiencing an increasing discrepancy between the coordination of their functions and the challenges they face. On the one hand, from the perspective of spatial planning policy, in addition to their role as regional supply, labour market and economic centres, they are charged with performing a stabilising function for the surrounding countryside and supporting the rural development dynamics. On the other hand, they are also under greater pressure to adapt their infrastructure to socio-economic change processes a pressure that must be handled. As a consequence, the maintenance and expansion of the performance capacity of medium-sized towns outside densely-populated areas are regarded as essential for the future compre-hensive provision of basic services in peripheral rural regions. The present book therefore firstly examines the regional stabilisation function of medium-sized towns in peripheral rural regions and includes an analysis of the possibilities and limits of their maintenance under the influence of socio-economic transformation processes and the associa-ted need for adaptation. Based on this, the second part consists of an analysis to identify suc-cess factors that will safeguard the stabilisation functions of medium-sized towns in rural peri-pheral areas in the future. To this end, this work initially focuses on defining and contextualising the concept of stabilisation in regional studies. Closely related to this is the analysis of state and regional planning and regio-nal economic approaches from the perspective of their stabilisation concept and the investigation of existing strategies for dealing with regional structural change processes. This is followed by an indicator-based or functional typification of the middle-sized town type in the context of the peripheral rural spatial type. In this context, five selected case studies are in-cluded for a deeper evaluation. This results in complementary findings, especially with regard to the interdependencies between the county region and the medium-sized town, the significance of the medium-sized town with regard to its centrality in terms of living, working and service supply, and in particular with regard to existing required actions and development strategies and initiatives to strengthen the function and role of the medium-sized town in and for its peripheral rural environment.
Keywords: Regionalplanung; Regionalwissenschaft; Raumstruktur; Ländlicher Raum; Peripherie; Strukturwandel; Mittelstadt; Stadttyp; Stabilisierung; Landkreis; Problemraum; Lebensbedingungen; Daseinsvorsorge; Grundversorgung; Verflechtung; Zentralität; Wohnort; Arbeitsort; Fallstudie; Kreisregion